Effect of three hours race walk on energy cost, cardiorespiratory parameters and stride duration in elite race walkers - Brisswalter, J.; Fougeron, B.; Legros, P. (International Journal of Sports Medicine, 1996)
The purpose of this study was to quantify changes in energy cost of walking (C), ventilation (VE), respiratory frequency (RF), heart rate (HR), expiratory ratio (RER), blood lactate concentration (LA), body mass (W) and stride duration (SD) after a 3 hour race walk at competition pace in elite race walkers. Subjects were tested during 2 submaximal treadmill tests at 12.2 +/- 0.5 km.h(-1) (74.7% VO2max speed) before and after a 3 hour overground walk. Significant increases (p < 0.05) were found in C, HR and significant decreases were found in RER, W, VE whereas no changes were observed in LA or SD (means and intra-subject variability). However, a wide range of individual coefficients of variation were observed for C, VE, RF, HR, SD, W. These results suggest that in well trained walkers the energy cost of walking increases with exercise duration but that walkers are able to maintain the same stride duration after the test when treadmill speed is controlled. Furthermore, some individuals appear to be more sensitive to fatigue. Discussion set out a possible effect of substrate utilisation changes, thermoregulation or a decrease in mechanical efficiency for maintaining the race walk gait apart from the effect of fatigue.